(untitled) (Andamios, Revista de Investigación Social, 2013)
The current political structure of contemporary Mexico cannot be fully understood but through an historical analysis of those who form one of its main institutions: local political parties, whose continuous founding moments encompass at least a whole generation. However, in parallel to the above, it is necessary to investigate, in addition to their originative moment, what is the level of legal openness of the norms that control their birth at the time of their registration, in order to identify, secondly, if during their foundational journey we may point out similarities between the rules prevailing in each state and some specific times of the national political life.